Barrett's oesophagus and associated dysplasia are not equally distributed within the esophageal circumference. Issue 9 (September 2016) - Bibbò, Stefano; Ianiro, Gianluca; Ricci, Riccardo; Arciuolo, Damiano; Petruzziello, Lucio; Spada, Cristiano; Larghi, Alberto; Riccioni, Maria Elena; Gasbarrini, Antonio; Costamagna, Guido; Cammarota, Giovanni
Abstract: Background: A careful endoscopic surveillance of Barrett's oesophagus is warranted to prevent esophageal cancer. Aim: To identify the preferred location of non-circumferential Barrett's oesophagus and associated dysplasia within the esophageal circumference. Methods: We retrospectively reviewed a prospectively maintained database of patients with non-circumferential lesions. The location of metaplastic lesions and dysplastic lesions within the esophageal circumference was identified as on a clock face, and their distribution in the 4 quadrants was compared. Results: Of overall 443 patients with Barrett's oesophagus, 192 (43%) were eligible for our study. Multiple lesions were diagnosed in 110 (57%) of them, for a total amount of 352 metaplastic areas. Barrett's oesophagus lesions were located significantly more in the posterior wall of the oesophagus (38.4%), rather than in the right wall (28.8%), the anterior wall (22.6%), or the left wall (10.2%) ( P < 0.0001). Among all metaplastic lesions, 28 were associated with dysplasia (7.9%), and one with adenocarcinoma (0.3%). Dysplastic lesions were significantly more common in the posterior wall (39.3%) than, respectively, in the anterior wall (35.8%), the right wall (21.4%) or the left wall (3.5%) ( P = 0.03). Conclusion: Our results show that the posterior wall of the oesophagus is the preferential location of both Barrett's oesophagus and associated dysplasia.